2018
DOI: 10.2519/jospt.2018.8038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compression Garments on the Development of Delayed-Onset Muscle Soreness: A Multimodal Approach Using Contrast-Enhanced Ultrasound and Acoustic Radiation Force Impulse Elastography

Abstract: Continuous wearing of compression garments during the inflammation phase of DOMS may play an important role in regulating muscle stiffness; however, compression garments have no significant effects on intramuscular perfusion or other common clinical assessments. J Orthop Sports Phys Ther 2018;48(11):887-894. Epub12 Jun 2018. doi:10.2519/jospt.2018.8038.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 37 publications
1
63
0
Order By: Relevance
“…Regarding the influence of post-exercise CWI on muscle stiffness, the efficiency seems to be dependent on the type of the previous exercise. The application of post-exercise CWI is a commonly used therapy to enhance recovery, and thereby to counteract EIMD or DOMS [3,4,15,18,32,33]. Particularly in elite sports, CWI is recommended by many physical therapists and coaches [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the influence of post-exercise CWI on muscle stiffness, the efficiency seems to be dependent on the type of the previous exercise. The application of post-exercise CWI is a commonly used therapy to enhance recovery, and thereby to counteract EIMD or DOMS [3,4,15,18,32,33]. Particularly in elite sports, CWI is recommended by many physical therapists and coaches [1].…”
Section: Discussionmentioning
confidence: 99%
“…As recommended, absolute shear wave velocities (SWV in m/s) were obtained in the representative ROI in longitudinal parallel axis of the muscle as recommended in order to avoid any anisotropic effects [20,21]. Ten measurement repetitions with 10 manually chosen ROI positioning based on the fixed field of view were assessed for each probe position and anatomical section, following previously published protocols [18,22,23]; mean values were considered. The probe position was marked during the first trial using a permanent marker to ensure identical probe positions for the following post-intervention trials (▶ Fig.…”
Section: Ultrasound Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies reported that compression garments reduced muscle oscillation and stabilized the array of muscle fibers during the recovery period, which could ease the mechanical stress on tissues [34,43,44]. Continuous wearing of compression garments (18 -21 mmHg) during the inflammation phase of DOMS (60 h) showed a premature normalization of muscle stiffness in the gastrocnemius muscle assessed with acoustic radiation force impulse [45]. Otherwise, the same authors reported no significant effect on the development of muscle edema and muscle soreness [45,46].…”
Section: Compression Therapy After Exercisementioning
confidence: 94%
“…Continuous wearing of compression garments (18 -21 mmHg) during the inflammation phase of DOMS (60 h) showed a premature normalization of muscle stiffness in the gastrocnemius muscle assessed with acoustic radiation force impulse [45]. Otherwise, the same authors reported no significant effect on the development of muscle edema and muscle soreness [45,46].…”
Section: Compression Therapy After Exercisementioning
confidence: 99%